Differentiation between major depressive disorder and bipolar disorder by auditory steady-state responses. - Isomura, Shuichi; Onitsuka, Toshiaki; Tsuchimoto, Rikako; Nakamura, Itta; Hirano, Shogo; Oda, Yuko; Oribe, Naoya; Hirano, Yoji; Ueno, Takefumi; Kanba, Shigenobu (Journal of Affective Disorders, 2016)
Background: The auditory steady-state response (ASSR) elicited by gamma band neural oscillations has received considerable interest as a biomarker of psychiatric disorders. Although recent ASSR studies have reported that patients with bipolar disorder (BD) show altered ASSRs, little is known about ASSRs in patients with major depressive disorder (MDD). The aim of this study was to evaluate whether ASSRs in MDD subjects differed from those in BD subjects or normal controls (NC).Method: We analyzed ASSRs in 14 MDD patients, 19 BD patients, and 29 normal control subjects. We used whole-head 306-channel magnetoencephalography to evaluate ASSR power and phase-locking factors (PLF) elicited by 20-, 30-, 40-, and 80-Hz click trains. We determined optimal sensitivity and specificity of ASSR power and PLF for the diagnosis of MDD or BD via receiver operating characteristic (ROC) curve analysis using a nonparametric approach.Results: MDD patients exhibited no significant differences in ASSR power or PLF compared with NC subjects, while BD patients showed deficits on the ASSR measures. MDD patients showed significantly larger ASSR power and PLF for 30-, 40-, and 80-Hz stimuli compared with BD patients. The area under the curve (AUC) for the ROC analysis (MDD vs. BD) was 0.81 [95% CI=0.66-0.96, p=0.003] concerning 40-Hz ASSR power.Limitations: We could not exclude the effect of medication and the sample size of the current study is relatively small.Conclusions: We could differentiate between MDD and BD subjects in terms of gamma band ASSR. Our data suggest that the 40-Hz ASSR may be a potential biomarker for differentiation between MDD and BD patients.